(untitled) (Revista de História Regional, 2023)
Although football was often seen as a symbol of modernity, progress, and civility, it also generated suspicions and rejections. In this text, we intend to shed light on little-known criticisms of the history of sport. These are those published in Lar Catholico, a Catholic weekly created by the Congregation of the Divine Word in 1919, in Juiz de Fora-MG. Our goal is to rescue the newspaper’s position in the 1920s and 1930s, identify the axis of its criticisms of football, and locate them in the context of disputes and trends that marked the period. In general, the criticisms of football and popular culture present in the newspaper reflect the fear of the Catholic elite regarding secular modernity. Football was seen as savage, dangerous, a moral threat capable of encouraging the profanation of Sunday, diverting young people from their virtues, and leading them to frivolous behavior. The defense of the faith and Christian values was, for the Congregation of the Divine Word, a way of resisting the secular project of modernization and continuing to exert influence on Brazilian families. Finally, we believe that our study indicates the existence of dissonant voices and nuances in the process of football diffusion in the interior of the country that cannot be ignored.